OPPORTUNITIES TO MAKE A SUSTAINABLE FREE NUTRITIONAL FOOD PROGRAM IN INDONESIA: A SCIENTIFIC IDEA - Teguh Yuwono; Milka Inkiriwang; Fikri Achmad Abdullah (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Efforts to realize the national goals enshrined in the Preamble to the 1945 Constitution must be carried out collaboratively, involving all elements of the nation, and prepared holistically, integrally, and comprehensively through the swift and appropriate utilization of national resources. In this regard, the state must play a significant role in managing the country based on the values ​​of Pancasila and the 1945 Constitution and for the greatest prosperity of the Indonesian people. The challenge is not insignificant, especially given its geographical location, which stretches from Sabang to Merauke, from Miangas Island to Rote Island, connected by waters and oceans. The existence of this archipelago demands a strong commitment to national development within the principle of Bhinneka Tunggal Ika (Unity in Diversity). It is through this diversity that the Unitary State of the Republic of Indonesia (NKRI) becomes stronger and more advanced. Development should be able to achieve a balance between the planet, people, and profit, as outlined in the Triple Bottom Line (TBL) Theory, introduced by John Elkington. This theory is a framework that measures company performance not only in terms of profit but also social (People) and environmental (Planet) impacts, to achieve long-term business sustainability, not just financial gain. Over time, TBL became the basis for the 1987 global framework for sustainable development established by a commission established by the United Nations (UN). This research design uses a descriptive qualitative approach with a thematic narrative approach to identify and describe research variables. Data were collected using a literature review method, then analyzed using qualitative methods based on similar themes and presented in narrative form. Hadiningrat et al. (2025) explain that qualitative research is a systematic, non-numerical method/technique or procedure for comprehensively and in-depth description of social phenomena in research. The study concluded that implementing the Sustainable Free Nutritious Meals (MBG) program in Indonesia offers significant potential because: a) the objectives of MBG align with sustainable development goals; b) MBG is part of an effort to prepare future generations for quality nutrition; c) MBG is a government intervention to address community nutrition issues to reduce disparities. And the most crucial challenge is to create a National Nutrition Law that includes provisions regarding the MBG, so that it continues regardless of who is president.